A Life Table of Spodoptera litura Fabr. with Different Artificial Diets - Sri Lestari; Trisnowati Budi Ambarningrum; Hery Pratiknyo (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2013)
Abstract Sustainable insect supply is a routine activity in research of pest control, experimental insecticide bioassay, entomophatogen, parasitoid, and nature of competitor. Armyworm (Spodoptera litura Fabr.) is one of the alternative test insect. A mass rearing method is required to provide high demands of S. litura. A life table of insect is regularly used to study several biological parameters including the net reproduction rate of population (Ro), the mean length of life period in one generation (T), reproduction potential value of one generation from a population (rm), and the potential of a population to multiply in one generation (ë). The aim of this study were to asses the development time and reproduction potential of S. litura which different of artificial diets. Results showed that S. litura on artificial diet in recipe of Singh and Moore is T = 29,90, R = 2692,33, r = 0,26, ë = 1,29, o m whereas artificial diet in recipe of Waldbauer et al. is 32,29, R = 891,99, r = 0,21, ë = 1,23. o m